Racial disparities in asthma-related health care use in the National Heart, Lung, and Blood Institute's Severe Asthma Research Program - Fitzpatrick, Anne M.; Gillespie, Scott E.; Mauger, David T.; Phillips, Brenda R.; Bleecker, Eugene R.; Israel, Elliot; Meyers, Deborah A.; Moore, Wendy C.; Sorkness, Ronald L.; Wenzel, Sally E.; Bacharier, Leonard B.; Castro, Mario; et al. (Journal of allergy and clinical immunology, 2019)
Despite advances in asthma care, disparities persist. Black patients are disproportionally affected by asthma and also have poorer outcomes compared with white patients. We sought to determine associations between black and white patients and asthma-related health care use, accounting for complex relationships. This study was completed as part of the National Heart, Lung, and Blood Institute's Severe Asthma Research Program, a prospective observational cohort. Between November 2012 and February 2015, it enrolled 579 participants 6 years and older with 1 year of observation time and complete data. Inverse probability of treatment weighting was used to balance racial groups with respect to community and family socioeconomic variables and environmental exposure variables. The primary outcome was emergency department (ED) use for asthma. Secondary outcomes included inhaled corticosteroid use, outpatient physician's office visits for asthma, and asthma–related hospitalization. Black patients had greater odds of ED use over 1 year (odds ratio, 2.19; 95% CI, 1.43-3.35) but also differed in the majority (>50%) of baseline variables measured. After statistical balancing of the racial groups, the difference between black and white patients with respect to ED use no longer reached the level of significance. Instead, in secondary analyses black patients were less likely to see an outpatient physician for asthma management (adjusted odds ratio, 0.57; 95% CI, 0.38-0.85). The disparity in ED use was eliminated after consideration of multiple variables. Social and environmental policies and interventions tailored to black populations with a high burden of asthma are critical to reduction (or elimination) of these disparities. [Display omitted]